An Error Analysis On Changing Active Voice Into Passive Voice At Ninth Grade Of Smp Amir Hamzah Medan - Bambang Nur Alamsyah Lubis; Tazari Putri Afrilyani; Sri Wahyuni Girsang; Bintang Mangasih Tua Sihite; Shandy Chandra; Agus Permadi (EDUTECH, 2019)
This study focuses to analyze the errors probably make on changing active voice into passive voice. Was the study was conducted at SMP YPI Amir Hamzah Medan. The subject of the research was class VIII consisted of 24 students. The type of research is quantitative research. Based on the problem study aimed (1) to to identify and analyze the errors probably make on changing active voice into passive voice. (2) to find out the dominant tense has more errors on changing active voice into passive voice. The instruments of data collection is test. The data were obtained and used in quantative form. Based on data analysis, researchers found that the total errors made by students were 277. The types of errors students made were ommission(56 or 20.22%), misformation (168 or 60.65%), addition (28 or 10.11%) and misordering (25 or 9.03 %). The data also shows that the dominant tense has more errorson changing active voice into passive voice is misformation